Novel Insights into the Physiological Function of the APP (Gene) Family and Its Proteolytic Fragments in Synaptic Plasticity - Ludewig, Susann; Korte, Martin (Frontiers in Molecular Neuroscience, 2017)
The amyloid precursor protein (APP) is well known to be involved in the pathophysiology of Alzheimer’s disease via its cleavage product amyloid ß (Aß). However, the physiological role of APP, its various proteolytic products and the amyloid precursor-like proteins 1 and 2 (APLP1/2) are still not fully clarified. Interestingly, it has been shown that learning and memory processes represented by functional and structural changes at synapses are altered in different APP and APLP1/2 mouse mutants. In addition, APP and its fragments are implicated in regulating synaptic strength further reinforcing their modulatory role at the synapse. While APLP2 and APP are functionally redundant, the exclusively CNS expressed APLP1, might have individual roles within the synaptic network. The proteolytic product of non-amyloidogenic APP processing, APPsα, emerged as a neurotrophic peptide that facilitates long-term potentiation (LTP) and restores impairments occurring with age. Interestingly, the newly discovered η-secretase cleavage product, An-α acts in the opposite direction, namely decreasing LTP. In this review we summarize recent findings with emphasis on the physiological role of the APP gene family and its proteolytic products on synaptic function and plasticity, especially during processes of hippocampal LTP. Therefore we focus on literature that provide electrophysiological data by using different mutant mouse strains either lacking full-length or parts of the APP proteins or that utilized secretase inhibitors as well as secreted APP fragments.